Working Capital Strategy and Operation Risk in the Food and Beverage Companies Listed in the Indonesia Stock Exchange - Junaidi, Junaidi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
The purpose of this study is to investigate the effect of working capital investment and working capital financing on the operational risk of nine listed firms in the agricultural sector of the Indonesian Stock Exchange. The time period used is 12 years from 2008 - 2019. The operational risk variable is the deviation absolute value of ROA, ROE, Sales and Cost of Goods Sold. The independent variable is the working capital investment strategy (WCIS) and Working Capital Financing Policy (WCFS). For control variables using debt ratio, size, age and current ratio variables. The analysis technique used is Ordinary Least Square (OLS) regression. The results obtained by shows that (1) WCIP have a negative and significant impact on the risk of ROA and ROE, (2) WCIP has a positive and significant effect on the risk of sales and CGS, (3) WCFP has a positive and significant impact on the risk of ROA and ROE, however, (4) WCFP has a negative and significant effect on the risk of sales and CGS. Debt ratio only has a positive effect on ROE risk. Company asset size has a positive and significant effect on Sales and CGS. Company age has a positive and significant effect on ROE risk. The current ratio variable has a positive effect on ROE risk and has a negative effect on the risk of sales and CGS.